1997
DOI: 10.1038/sj.sc.3100436
|View full text |Cite
|
Sign up to set email alerts
|

Postural hypotension and abnormalities of salt and water metabolism in myelopathy patients

Abstract: To describe the clinical manifestations of postural hypotension (PH) in myelopathy patients a standardized interview and chart review were carried out. Of 232 myelopathy patients with more than 2 years of paralysis seen during a 2 year period, 30 had been treated for PH. All PH patients were paralysed at levels higher than thoracic 7. The highest risk patients were tetraplegic, motor complete, 24 of 73 (33%). The common symptoms of PH were those of reduced consciousness (100%), strength (75%), vision (56%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 16 publications
(20 reference statements)
0
34
0
1
Order By: Relevance
“…66 In patients with chronic SCI, there is evidence of impaired water and sodium retention in the seated position, and limited salt and water intake. 25,74 Hyponatremia is also reported in acute SCI. 75 Thus, hyponatremia, probably secondary to supraphysiological ADH activity in SCI, 51 is common among acute and chronic SCI patients.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
See 2 more Smart Citations
“…66 In patients with chronic SCI, there is evidence of impaired water and sodium retention in the seated position, and limited salt and water intake. 25,74 Hyponatremia is also reported in acute SCI. 75 Thus, hyponatremia, probably secondary to supraphysiological ADH activity in SCI, 51 is common among acute and chronic SCI patients.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
“…6 However, it has also been shown that autonomic dysreflexia can present in the early phases of SCI, 23,24 and that orthostatic hypotension can persist for years, and often becomes worse with time. 25 Numerous investigators identified various possible mechanisms that are likely to be responsible for the abnormal sympathetic cardiovascular control following SCI (Table 1). Firstly, there is a loss of descending supraspinal sympathetic excitatory and inhibitory control.…”
Section: Physiology and Neuroanatomy Of Cardiovascular Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Both of these responses are clinically recognized in patients with the higher, more extensive spinal cord lesions. 3,4 It is reasonable to suspect that BP is unstable subclinically as well in the tetraplegic patient. This expectation is supported by the unstable cutaneous blood flow recently demonstrated in asymptomatic tetraplegic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Attention to both salt and water metabolism in patients with the syndrome described could improve circulation to critical areas such as the brain, the skin, the kidneys, and the lungs. 35 …”
Section: Discussionmentioning
confidence: 99%